Assistance in the Use of the Sigenduk Application in Lamongan Regency to Improve Public Services - Nadhifah, Nurul Asiya; Musyafaah, Nur Lailatul; Rohmah, Elva Imeldatur; Rohman, Moh. Faizur (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
The implementation of a Village Information System (SID) in public services is regulated in Law Number 6 of 2014 concerning Villages. However, many villages in Lamongan regency have not used the application due to various factors, even though in Lamongan there is a SID application called SIGENDUK (Superior Village Movement Information System with Character). This article discusses assistance in the use of the SIGENDUK application to improve public services in Lamongan district. Assistance was carried out in three villages in Lamongan regency, namely RejoTengah, Kendalkemlagi and Menongo, because the three villages have not used the SIGENDUK application in public services. Assistance is carried out using the Participatory Action Research (PAR) method. The assistance results concluded that the village government did not use the SID application because there was no socialization and training on SID, there was a lack of human resources who were technology experts and because of costs. On the other hand, the Lamongan Regency Government has a SID application called SIGENDUK which can be used for free. Based on this, socialization and training on the SIGENDUK application were held for residents and village officials. With this socialization and training, the village government has access rights to use the SIGENDUK application and devices to serve various administrative and data storage services.